Conceptual Metaphors and Conceptual Frames in Barasuara's "Terbuang Dalam Waktu": A Cognitive Linguistic Analysis Based on Lakoff and Johnson's Conceptual Metaphor Theory - Nensilianti; Ridwan; Azharina (Wanastra: Jurnal Bahasa dan Sastra, 2026)
This study aims to identify the forms of metaphor and conceptual frames in the lyrics of “Terbuang dalam Waktu” by Barasuara and explain how these metaphors construct meanings about time, loss, and existence. This study employs a descriptive qualitative approach based on George Lakoff’s conceptual metaphor theory, encompassing structural, ontological, and orientational metaphors. Data were collected through close reading and note-taking techniques and analysed by identifying metaphorical expressions and mapping the source and target domains. The findings indicate that time is primarily understood through the conceptual metaphors “time is a force” and “time is space,” which depict time as a concrete and powerful entity capable of “removing” humans. In contrast to previous studies that mainly classified types of metaphor, this study also examines how metaphor constructs broader conceptual frameworks related to time, loss, and existential experience. This conceptualisation reveals how metaphorical expressions construct meanings related to time, loss, and existential experience, as well as demonstrating the cognitive role of metaphor in the analysed song lyrics.